IoT Enabled Smart Bin for Waste Management with Incentivized Rewards - B, Bhavya; R, Farshan M; B, Nikkitha; A, Rana V; K, Nisna Haneefa (Journal of ISMAC, 2024)
Improper waste management plagues the earth, posing serious environmental and health threats. Traditional bins lack the ability to segregate waste at the source, further exacerbating the problem. This ingenious system tackles two major challenges: inefficient waste segregation and lack of motivation for proper disposal. Equipped with sensors and camera, the smart bin automatically identifies and segregates different waste types, ensuring cleaner waste streams. The system employs a unique reward-based mechanism to incentivize responsible waste disposal. This research is mainly focused to improve the environmental sustainability by providing reward system. This reward system encourages the people to deposit plastic waste properly to the bin, hence it creates a disposal behaviour among the public.